Martin Luther King: the peaceful warrior. - Clayton, Ed, 1921-1966.; Hodges, David (Englewood Cliffs, N.J., Prentice-Hall, 1964)
A biography of the black leader, Martin Luther King, who, encouraged by the teachings of Mahatma Gandhi, inspired the Nation to begin a non-violent campaign for equality.
includes bibliography
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968.